Market-oriented smallholder development—IPMS experience-sharing workshop - International Livestock Research Institute (International Livestock Research Institute, 2011)
To help achieve the Growth and Transformation Plan (GTP) which Ethiopia is implementing, The International Livestock Research Institute (ILRI) through the Improving Productivity and Market Success of Ethiopian Farmers project (IPMS) is proving professional support to smallholder farmers. This is believed to enable smallholder farmers to change their way of production from daily consumption to market-oriented production. During the workshop, Dr Edemalem Shitaye, delegate from the Ministry of Agriculture (MoA), said that market-oriented agricultural production system has a significant role to achieve the GTP. ILRI’s Deputy Director General, Dr John McDermott noted that the IPMS project is working towards the transfer of significant lessons and experiences gained by participatory market-oriented development. Mr Edmond Wega, CIDA director for Ethiopia and head of development cooperation, said that to bring about growth and development there is a need to produce market-oriented agricultural products and become competitive in the international market.